(untitled) (Revista LIDER, 2018)
This study focusses on the urban environmental policy of the municipality of Mossoró / RN and its social actors. The social actors studied here are the Municipal Environmental Council, the City Council, and the Municipal Management of Mossoró. The methodology consisted in the use of the social cartography system in order to capture the sense of experiences for the construction of new ways of management performance of the urban environment. The study analyzes different understandings of the social and environmental reality of the city of Mossoró / RN and the requirements for participation in the decision-making processes of urban environmental management. The findings suggest the need for more efforts to strengthen the culture of participation through greater knowledge of civil society in order to participate in a more efficient and effective management.